Strategi Pengembangan dan Pemasaran Produk Menggunakan Sentra Wisata Kuliner UMKM Minuman di Kelurahan Keputih Kecamatan Sukolilo Kota Surabaya - Asnanda Fairuz Tsuraya; Yanda Bara Kusuma (Jurnal Masyarakat Mengabdi Nusantara, 2023)
For approximately 3 months, these programs can be carried out well and can be accepted by the residents of Keputih Village even though there are several obstacles or obstacles that become a challenge for students to find solutions to these problems so that the planned programs can run more optimally and are expected to help develop MSMEs and business potential in Keputih Village, Sukolilo District, Surabaya City well. The Thematic Real Work Lecture of Merdeka Belajar Kampus Merdeka (KKNT MBKM) has a work program that has been implemented by the University of National Development "Veteran" East Java. This work program includes FGD (Focus Group Discussion), Ramadan bazaar and coloring competition as well as takjil distribution, counseling, training, TTG innovation which is called by another term, namely Appropriate Technology. This TTG is also in the form of a map of the potential of MSMEs in Keputih Village and a menu catalog of the Harmoni Keputih Tourism Market, an exhibition of Baverage Culinary Tourism Center Activities and an exhibition of MSMEs in Sukolilo District, the creation of a website for the Harmoni Keputih Tourism Market, the creation of the Harmoni Keputih Tourism Market Instagram, and the creation of product promotion content for MSMEs in the Keputih region.